Lowering the Dietary Crude Protein Content Whilst Maintaining Standardized Ileal Digestible Lysine to Crude Protein Ratios Improves Growth and Reduces Diarrhoea in Weaner Pigs - James E. Langley; Kate J. Plush; Surinder S. Chauhan; John R. Pluske; Sally Tritton; Frank R. Dunshea; Jeremy J. Cottrell (Agriculture, 2025)
The use of lower crude protein (CP) diets immediately after weaning has long been associated with reduced post-weaning diarrhoea (PWD). However, failing to maintain an appropriate standardized ileal digestible lysine ratio (SID: Lys) may outweigh the benefits in improving PWD outcomes. In this experiment, 560 weaners were fed either a control diet (CON; 20.6% crude protein 1.34% standardized ileal digestible lysine, SID Lys: CP = 0.06), LH: a low crude protein, higher SID Lys: CP ratio diet (19.0% CP, 1.34% SID Lys, SID Lys: CP = 0.07), or LL: a low crude protein control SID Lys: CP ratio diet (18.7% CP, 1.1% SID Lys, SID Lys: CP = 0.05) for 1 week after weaning. Pigs were scored for the presence or absence of diarrhoea for 12 days after weaning. Blood samples were taken on days 5, 12 and 28 for inflammatory marker analyses and plasma creatinine analyses. Relative to the CON diet, there was a 42% reduction in the diarrhoea index in pigs fed the LH diet and a 63% reduction in those fed the LL diet (p < 0.05), but LH was significantly higher than LL. There tended to be a greater average daily gain in the LH diet in the first week post-wean (p = 0.054). In summary, lower crude protein diets, irrespective of Lys: CP ratio, were found to be effective at reducing PWD. Moreover, increasing the SID Lys: CP ratio by reducing the CP content of diets from 20.6 to 19% appeared to improve post-weaning growth.